2016
DOI: 10.1002/adfm.201504211
|View full text |Cite
|
Sign up to set email alerts
|

Thin Film Growth of nbo MOFs and their Integration with Electroacoustic Devices

Abstract: Metal‐organic frameworks (MOFs) with the “nbo” topology constitute a diverse suite of more than 100 nanoporous materials, but their use in applications such as chemical sensing and membranes is inhibited by a lack of methods for growing them as thin films. Here, layer‐by‐layer (LBL) and solvothermal growth of “nbo” films is demonstrated and it is established for the first time that interlinker steric hindrance is a critical factor in determining the effectiveness of the LBL method. Film growth is demonstrated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
41
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 47 publications
0
41
0
Order By: Relevance
“…The R a of MIL-101(Cr), NH 2 -MIL-101(Cr), and NO 2 -MIL-101(Cr) thin films are only 3.4, 3.0, and 4.2 nm, respectively. The R q of them are 4.4, 3.8, and 5.5 nm, which are smaller than those of MOF-based thin films in previous reports [18,34,35]. For instance, Demessence et al [18] reported that the root-mean-square roughness of MIL-101(Cr) optical thin films was calculated to be around 12 nm (nearly half of the MOF NP diameter).…”
Section: Fabrication Of Mof-based Optical Thin Filmsmentioning
confidence: 68%
“…The R a of MIL-101(Cr), NH 2 -MIL-101(Cr), and NO 2 -MIL-101(Cr) thin films are only 3.4, 3.0, and 4.2 nm, respectively. The R q of them are 4.4, 3.8, and 5.5 nm, which are smaller than those of MOF-based thin films in previous reports [18,34,35]. For instance, Demessence et al [18] reported that the root-mean-square roughness of MIL-101(Cr) optical thin films was calculated to be around 12 nm (nearly half of the MOF NP diameter).…”
Section: Fabrication Of Mof-based Optical Thin Filmsmentioning
confidence: 68%
“…At present, most of the well‐known crystalline‐oriented thin films are fabricated by this method. A number of MOF films contain the SBU's like dimeric species (SBU: secondary building unit, such as copper paddlewheel unit) or some containing more than one type of ligands have been developed by this method, such as [Cu 2 (ndc) 2 (dabco)] . This method can be used to prepare the highly oriented thin film of MOFs with 2D layered structure, such as [M 2 (bdc) 2 (H 2 O) 2 ] (M: Zn 2+ , Cu 2+ ; bdc: benzdicarboxylate).…”
Section: Methods For Fabrication Of Oriented Mof Thin Filmmentioning
confidence: 99%
“…Modular architecture of MOFs allows for regulation of network topology, structure metrics, along with coordination chemistry, which holds striking promise in extensive applications such as sensing, catalysis, gas storage, energy, and molecular separations . Nevertheless, given the relevance between reaction parameters and synthetic outcome, it can always be hard to predict the size, morphology, distribution, and orientation of targeted MOFs . More importantly, progress in these applications especially for electrochemical devices and biosensing system has been restricted by poor conductivity, slow diffusion and transfer of guest molecules, and powdered form .…”
Section: Introductionmentioning
confidence: 99%